Meningkatkan Kepercayaan Diri Anak Melalui Reward Asyik Pada Kelompok Tk B SPS Negeri Bale Bermain Pulau Sabira - Komariah, Komariah; Watini, Sri; Rizawati, Rizawati (Neolectura, 2025)
Self-confidence is a fundamental aspect of early childhood personality development, influencing children’s readiness for social interaction, learning, and independent task completion. UNICEF (2022) highlights that children with higher self-confidence are more adaptive to challenges, more sociable, and better prepared for formal education. In Indonesia, strengthening character and personality has been emphasized in the Merdeka Curriculum and Early Childhood Education (PAUD) programs, including at the kindergarten level. Nevertheless, data from the Ministry of Education and Culture (2021) indicate that over 40% of children aged 4–6 still demonstrate low self-confidence, particularly in remote island regions with limited resources. This study applied Classroom Action Research (CAR) in TK B SPS Negeri Bale, aiming to enhance self-confidence through the implementation of Reward Asyik during Sabira Island play activities. The results revealed significant improvement across two cycles, where in Cycle I only 15–30% of children reached the Developing Very Well (BSB) category and the Undeveloped (BB) category remained high at 25–10%, while in Cycle II the proportion of children in the BSB category increased to 20–40% and the BB category dropped sharply to 5%. These findings suggest that well-designed and enjoyable rewards can effectively foster self-confidence, encouraging children to actively participate, take initiative, and engage more confidently in learning activities.